Lanthanum-molybdenum composite oxide, antibacterial sintered body and antiviral sintered body

The lanthanum-molybdenum composite oxide, with La2Mo2O9 as the main phase and specific sub-phases, addresses the limitations of existing materials by offering enhanced antibacterial and antiviral properties, ensuring effective performance across different forms and environments.

JP7617588B2Active Publication Date: 2025-01-20INSTITUTE OF SCIENCE TOKYO +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020106727
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-06-22
Publication Date
2025-01-20
Estimated Expiration
2040-06-22

AI Technical Summary

Technical Problem

Existing antibacterial and antiviral materials, such as metal-based and photocatalytic materials, face issues with stability, cost, and light dependency, while composite oxides like La2Mo2O9 show room for improvement in their properties.

Method used

A lanthanum-molybdenum composite oxide with La2Mo2O9 as the main crystal phase and specific sub-crystalline phases, such as La2Mo3O12, La6MoO12, La7Mo7O30, La2Mo4O15, La2MoO6, and LaMo2O5, exhibits enhanced antibacterial and antiviral properties.

Benefits of technology

The composite oxide demonstrates superior antibacterial and antiviral performance against various bacteria and viruses, maintaining effectiveness in both powder and sintered forms, with improved stability and cost-effectiveness compared to existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617588000003
    Figure 0007617588000003
  • Figure 0007617588000004
    Figure 0007617588000004
  • Figure 0007617588000005
    Figure 0007617588000005
Patent Text Reader

Abstract

To provide a lanthanum-molybdenum complex oxide etc. which has both an excellent antibacterial property and antiviral property.SOLUTION: A lanthanum-molybdenum complex oxide comprises La2Mo2O9 as a main crystalline phase and a lanthanum-molybdenum complex oxide other than the La2Mo2O9 as a secondary crystalline phase. The main crystalline phase and the secondary crystalline phase in the lanthanum-molybdenum complex oxide can be specified by analyzing an X-ray diffraction spectrum obtained by powder X-ray diffractometry.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lanthanum-molybdenum composite oxide, an antibacterial sintered body, and an antiviral sintered body. [Background technology]

[0002] Inorganic materials with antibacterial and antiviral properties are known, including, for example, metal materials such as Ag and Cu, metal oxide materials such as ZnO and CaO, and photocatalytic materials such as TiO2.

[0003] However, metal-based materials such as Ag have a problem in that they are easily inactivated over time. Ag is particularly expensive, which has caused cost problems. Metal oxide-based materials also have a problem in that they have lower antibacterial properties than metal-based materials. Photocatalyst-based materials also have a problem in that they cannot exhibit antibacterial properties in an environment without light.

[0004] Due to these circumstances, ceramics made of La2Mo2O9 have been provided as a new type of inorganic material with antibacterial and antiviral properties (see Non-Patent Document 1). La2Mo2O9 is a composite oxide containing lanthanum and molybdenum, and has attracted attention as a new material with both antibacterial and antiviral properties. Lanthanum is inexpensive among rare earth elements and is easily available. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Takumi Matsumoto, et al., "Preparation of hydrophobic La2Mo2O9 ceramics with antibacterial and antiviral properties", Journal of Hazardous Materials, Elsevier Science, Netherlands, volume 378, 15 October 2019, article 120610 Summary of the Invention [Problem to be solved by the invention]

[0006] Although composite oxides containing lanthanum and molybdenum have both antibacterial and antiviral properties, there is room for further improvement in these antibacterial and antiviral properties.

[0007] The object of the present invention is to provide a lanthanum-molybdenum composite oxide having both excellent antibacterial and antiviral properties. [Means for solving the problem]

[0008] As a result of intensive research into achieving the above-mentioned object, the inventors have found that a lanthanum-molybdenum composite oxide having La2Mo2O9 as a main crystal phase and a lanthanum-molybdenum composite oxide other than La2Mo2O9 as a minor crystal phase has both excellent antibacterial and antiviral properties, which led to the completion of the present invention.

[0009] The means for solving the above problems are as follows. <1> A lanthanum-molybdenum composite oxide having La2Mo2O9 as a main crystal phase and a lanthanum-molybdenum composite oxide other than La2Mo2O9 as a secondary crystal phase.

[0010] <2> The secondary crystalline phase is La2Mo3O 12 , La6MoO 12 , La7Mo7O 30 , La2Mo4O 15, La2MoO6, La4MoO9 and LaMo2O5. <1> 2. The lanthanum-molybdenum composite oxide according to claim 1 .

[0011] <3> the ratio of the intensity X of the largest diffraction peak among the diffraction peaks attributable to the main crystalline phase that do not overlap with peaks of the sub crystalline phase in an X-ray diffraction spectrum obtained by a powder X-ray diffraction method to the intensity Y of the largest diffraction peak among the diffraction peaks attributable to the sub crystalline phase that do not overlap with the main crystalline phase is Y / X<1; <1> or <2> 2. The lanthanum-molybdenum composite oxide according to claim 1 .

[0012] <4> The above <1> from <3> An antibacterial sintered body obtained by sintering the lanthanum-molybdenum composite oxide described in any one of the above.

[0013] <5> The above <1> from <3> An antiviral sintered body obtained by sintering the lanthanum-molybdenum composite oxide described in any one of the above. Effect of the Invention

[0014] According to the present invention, it is possible to provide a lanthanum-molybdenum composite oxide and the like having excellent antibacterial and antiviral properties. [Brief description of the drawings]

[0015] [Figure 1] X-ray diffraction spectrum of the lanthanum-molybdenum composite oxide powder of Example 1 [Diagram 2] X-ray diffraction spectrum of the lanthanum-molybdenum composite oxide powder of Example 2 [Diagram 3] X-ray diffraction spectrum of the lanthanum-molybdenum composite oxide powder of Example 3 [Figure 4] X-ray diffraction spectrum of lanthanum-molybdenum composite oxide powder in Comparative Example 2 [Diagram 5] X-ray diffraction spectrum of the sintered body of Example 1 [Figure 6] X-ray diffraction spectrum of the sintered body of Example 2 [Figure 7] X-ray diffraction spectrum of the sintered body of Example 3 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] [Lanthanum-molybdenum mixed oxide] The lanthanum-molybdenum composite oxide of this embodiment is a composite oxide of lanthanum (La) and molybdenum (Mo) having La2Mo2O9 as a main crystal phase and a lanthanum-molybdenum composite oxide other than La2Mo2O9 as a secondary crystal phase.

[0017] As the lanthanum-molybdenum composite oxide other than La2Mo2O9 (i.e., as the secondary crystal phase), La2Mo3O 12 , La6MoO 12 , La7Mo7O 30 , La2Mo4O 15 It is preferable that the composition contains at least one selected from the group consisting of La2MoO6, La4MoO9 and LaMo2O5.

[0018] The secondary crystalline phase is, in particular, La2Mo3O 12 , La6MoO 12 , La7Mo7O 30 and LaMo2O5.

[0019] Note that the lanthanum-molybdenum composite oxide of this embodiment contains, as a secondary crystal phase, a lanthanum-molybdenum composite oxide other than La2Mo2O9, which may be referred to as a "lanthanum-molybdenum secondary composite oxide." Also, the lanthanum-molybdenum composite oxide of this embodiment contains, as a primary crystal phase, La2Mo2O9, which may be referred to as a "lanthanum-molybdenum primary composite oxide."

[0020] The lanthanum-molybdenum composite oxide may be in the form of a powder, or may be in the form of a sintered body obtained by sintering the powder.

[0021] The main and sub-crystalline phases in lanthanum-molybdenum oxides can be identified by analyzing the X-ray diffraction spectrum of the lanthanum-molybdenum oxides obtained by powder X-ray diffraction.

[0022] As described later, the crystalline phase resulting from the three diffraction peaks in descending order of intensity in the obtained X-ray diffraction spectrum is defined as the main crystalline phase, and the spectra other than the spectrum of the main crystalline phase are defined as the sub-crystalline phase. 12 etc.) are identified as La2Mo2O9 and La2Mo3O 12 This is done by comparison with known X-ray diffraction spectrum data such as those listed above.

[0023] In the lanthanum-molybdenum composite oxide of the present embodiment, the ratio of the intensity X of the largest diffraction peak among the diffraction peaks attributable to the main crystal phase that do not overlap with any peaks of the sub crystal phase in an X-ray diffraction spectrum obtained by powder X-ray diffraction method to the intensity Y of the largest diffraction peak among the diffraction peaks attributable to the sub crystal phase that do not overlap with any peaks of the main crystal phase satisfies Y / X<1.

[0024] The lanthanum-molybdenum composite oxide of the present embodiment is produced through the preparation step and firing step described below.

[0025] The preparation step is a step of mixing a lanthanum compound and a molybdenum compound to prepare a mixed powder.

[0026] The lanthanum compound is a compound containing lanthanum (La) necessary for producing a lanthanum-molybdenum composite oxide, and examples thereof include La(OH)3, La2O3, and La2(CO3)3. As the lanthanum compound, for example, at least one selected from the group consisting of La(OH)3, La2O3, and La2(CO3)3 may be used. As the lanthanum compound, La(OH)3 is preferred.

[0027] The molybdenum compound is a compound containing molybdenum (Mo) necessary for producing a lanthanum-molybdenum composite oxide, and examples thereof include MoO3, MoO2, MoO, Mo(OH)3, and Mo(OH)5. As the molybdenum compound, for example, at least one selected from the group consisting of MoO3, MoO2, MoO, Mo(OH)3, and Mo(OH)5 may be used. As the molybdenum compound, MoO3 is preferred.

[0028] The mixing ratio of the lanthanum compound and the molybdenum compound is preferably adjusted so that the molar ratio of La:Mo is 1:1.

[0029] The lanthanum compound and the molybdenum compound are mixed with each other in a solid phase. The lanthanum compound and the molybdenum compound are both powders, and may be mixed in the powder state, or a solvent such as a lower alcohol (ethanol) may be added to the powders to perform wet mixing. The lanthanum compound and the molybdenum compound may be mixed by wet mixing using, for example, alumina balls (alumina boulders). The wet-mixed mixture (wet mixture) is appropriately dried by water bath drying, spray drying, or the like.

[0030] By such a preparation process, a mixed powder of the lanthanum compound and the molybdenum compound is obtained.

[0031] The firing step is a step of firing the mixed powder obtained in the preparation step in a solid phase state. For example, the firing step is a step of firing the mixed powder in a solid phase state at a temperature condition of 500°C to 700°C for 2 hours or more. The firing step does not need to be performed in a special synthetic air atmosphere, but is performed in a normal air atmosphere.

[0032] By this firing step, the solid-phase lanthanum compound and the solid-phase molybdenum compound in the mixed powder react with each other to form a powder containing La2Mo2O9 as a main crystal phase and La2Mo3O as a sub crystal phase.12 Thus, a powdered lanthanum-molybdenum composite oxide (lanthanum-molybdenum composite oxide powder) containing the above is obtained.

[0033] In this specification, the firing step performed to react the lanthanum compound and the molybdenum compound in the mixed powder is sometimes referred to as the “first firing step.” This first firing step is a firing step (calcination step) performed before the lanthanum-molybdenum composite oxide powder is sintered.

[0034] After the firing step, a lanthanum-molybdenum composite oxide powder is obtained. The obtained lanthanum-molybdenum composite oxide powder may be granulated as necessary. For example, a solvent such as ethanol is added to the obtained lanthanum-molybdenum composite oxide powder, and wet mixing and grinding is performed using alumina balls or the like to prepare a slurry, and the dried slurry is passed through a sieve with a specified mesh size to obtain a lanthanum-molybdenum composite oxide powder granulated to a specified size.

[0035] The lanthanum-molybdenum composite oxide powder may also be sintered to form a sintered body. For example, the lanthanum-molybdenum composite oxide powder is molded into a predetermined shape (e.g., cylindrical, disk, etc.) using a predetermined press, and the molded body obtained is fired under a predetermined temperature condition (e.g., 900°C or higher) to sinter the powder, thereby obtaining a sintered body of the lanthanum-molybdenum composite oxide powder.

[0036] In this specification, the firing step performed to sinter the lanthanum-molybdenum composite oxide powder may be referred to as the “second firing step.” This second firing step is a main firing step performed to sinter the lanthanum-molybdenum composite oxide powder, and can be performed in an air atmosphere.

[0037] The lanthanum-molybdenum composite oxide of this embodiment exhibits antibacterial properties (antibacterial activity) and antiviral properties (antiviral activity) in the powder state before sintering (i.e., lanthanum-molybdenum composite oxide powder). Furthermore, the lanthanum-molybdenum composite oxide of this embodiment exhibits antibacterial and antiviral properties even after sintering, similar to those before sintering. The method for evaluating the antibacterial and antiviral properties of the lanthanum-molybdenum composite oxide will be described later.

[0038] Lanthanum-molybdenum composite oxide exhibits antibacterial properties against Staphylococcus aureus (gram-positive bacteria) and Escherichia coli (gram-negative bacteria), etc. It is also speculated that lanthanum-molybdenum composite oxide exhibits antibacterial properties against Klebsiella pneumoniae, methicillin-resistant Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and multidrug-resistant Pseudomonas aeruginosa, etc.

[0039] Lanthanum-molybdenum complex oxide also exhibits antiviral properties against bacteriophage Qβ, bacteriophage φ6, etc. Bacteriophage Qβ has no envelope and is known as an alternative virus to norovirus, while bacteriophage φ6 has an envelope and is known as an alternative virus to influenza virus. Lanthanum-molybdenum complex oxide is also presumed to exhibit antiviral properties against feline calicivirus (an alternative to human norovirus), human influenza virus, hog cholera virus, bovine viral diarrhea virus, border disease virus, kirchin petivirus, coronavirus, avian influenza virus, etc.

[0040] In addition, the lanthanum-molybdenum composite oxide of this embodiment is water repellent.

[0041] The lanthanum-molybdenum composite oxide of the present embodiment may be used as it is in a powder state (lanthanum-molybdenum composite oxide powder), or the lanthanum-molybdenum composite oxide powder may be mixed with other materials such as paints, resins, etc. As described above, the lanthanum-molybdenum composite oxide may be used in the state of a sintered body.

[0042] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples in any way.

[0043] Example 1 (Preparation of lanthanum-molybdenum composite oxide powder by solid-state method) La(OH)3 was prepared as the lanthanum compound, and MoO3 was prepared as the molybdenum compound. Then, the raw powder of the lanthanum compound and the raw powder of the molybdenum compound were weighed out so that the molar ratio was 1:1 (La:Mo=1:1). The weighed raw powders were mixed with a predetermined amount of ethanol, and the resulting wet mixture was dried to obtain a mixed powder. In the mixed powder, the lanthanum compound in a solid phase and the molybdenum compound in a solid phase were mixed together.

[0044] Next, the mixed powder was calcined in an air atmosphere at a temperature of 550° C. for 10 hours to obtain a calcined powder consisting of a reaction product of the lanthanum compound and the molybdenum compound (first calcination step). Then, the following operation was carried out to granulate the obtained calcined powder.

[0045] The mixture was placed in a resin pot together with a predetermined amount of ethanol, and the mixture was subjected to wet mixing and grinding using alumina balls to obtain a slurry.

[0046] The resulting slurry was then dried at 80°C for approximately 2 hours, and the resulting dried material was passed through a sieve with 250 μm mesh to obtain the lanthanum-molybdenum composite oxide powder of Example 1 as a granulated powder.

[0047] (Preparation of sintered body) The granulated lanthanum-molybdenum composite oxide powder was powder press molded using a specified press (molding pressure: 98 MPa), and then subjected to CIP (cold isostatic pressing) at a pressure of 150 MPa to obtain a disk-shaped molded body (diameter: 17 mm, thickness: 2.5 mm). The molded body was then fired at a temperature of 900°C for 10 hours in an air atmosphere to obtain a sintered body (second firing step). The obtained sintered body was further polished to obtain a sintered body of Example 1 (diameter: 15 mm, thickness: 2.0 mm disk-shaped) for evaluation of contact angle, etc., which will be described later.

[0048] Example 2 The lanthanum-molybdenum composite oxide powder of Example 2 was produced in the same manner as in Example 1, except that the sintering temperature of the mixed powder was changed to 600° C. in the manufacturing process of the granulated lanthanum-molybdenum composite oxide powder. Then, the sintered body of Example 2 (sintered body for evaluation) was produced by the same method as in Example 1 using the lanthanum-molybdenum composite oxide powder.

[0049] Example 3 The lanthanum-molybdenum composite oxide powder of Example 3 was produced in the same manner as in Example 1, except that the sintering temperature of the mixed powder was changed to 650°C in the manufacturing process of the granulated lanthanum-molybdenum composite oxide powder. Then, the sintered body of Example 3 (sintered body for evaluation) was produced in the same manner as in Example 1 using the lanthanum-molybdenum composite oxide powder.

[0050] Comparative Example 1 The powder and sintered body prepared by the complex polymerization method described in Non-Patent Document 1 are shown as Comparative Example 1. The method for preparing the powder and sintered body of Comparative Example 1 is as described in Non-Patent Document 1, and will be briefly described below.

[0051] 2.503 g of La(NO3)3 6H2O and 1.021 g of (NH4)6Mo7O 24A mixed solution was prepared by dissolving 10 ml of lanthanum ions and 4H2O in 10 ml of distilled water. The molar ratio of lanthanum ions and molybdenum ions in the mixed solution was 1:1. Next, citric acid and ethylene glycol were added to the mixed solution. The molar ratio of the combined metal ions (lanthanum ions and molybdenum ions) to citric acid in the mixed solution was 1:2. The molar ratio of ethylene glycol to citric acid in the mixed solution was 2:3.

[0052] The mixed solution was stirred at 80° C. for 6 hours to obtain a gel-like precursor. The precursor was dried at 200° C. for 24 hours, and then the dried precursor was pulverized for 10 minutes using a mortar and pestle. The pulverized product was then fired at 500° C. for 12 hours to obtain the powder of Comparative Example 1.

[0053] (Preparation of sintered body) The powder was mixed with 2% by volume of ethylene glycol as a binder and uniaxially pressed at 100 MPa for 3 minutes to obtain a compact (pellet) with a diameter of 10 mm. The compact was fired for 12 hours at a temperature of 900°C in a specified synthetic air atmosphere to obtain a sintered body. The synthetic air was a mixed gas of nitrogen (80%) and oxygen (20%), and was supplied at a flow rate of 1.0 L / min.

[0054] Comparative Example 2 A granulated powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that the firing temperature of the mixed powder was changed to 800°C.

[0055] [Identification of crystalline phases using powder XRD (1)] For the powders (before sintering) of each of the examples obtained after the first firing, the main crystal phase and the sub crystal phase in the crystal phase were identified using powder X-ray diffraction (XRD). The measurement conditions were as follows.

[0056] <Measurement conditions> Measurement equipment: Powder X-ray diffraction equipment (equipment name "Smart lab", manufactured by Rigaku Corporation) Detector: D / teX Ultra250. Optical system: Bragg-Brentano type centralized optical system X-ray output: 40kV-30mA Step width: 0.0200° Scanning axis: 2θ / θ Scanning range: 10.00°~80.00° Rotation: Yes

[0057] <Definition of main and sub crystalline phases> In the obtained X-ray diffraction spectrum, the crystalline phase resulting from the three diffraction peaks in descending order of intensity was defined as the main crystalline phase (main phase), and the spectra other than the spectrum of the main crystalline phase were defined as the sub-crystalline phase.

[0058] The results of X-ray diffraction spectrum (before sintering) of each Example are shown in Fig. 1 to Fig. 4, and the results of identifying the crystal phase are shown in Table 1. Note that, for the results of Comparative Example 1, reference was made to the description in Non-Patent Document 1. Note that, for the evaluation results of Comparative Example 1 described later, reference was made to the description in Non-Patent Document 1.

[0059] [Impurity content] The content of impurities composed of elements other than lanthanum and molybdenum in the powders (before sintering) of each example obtained after the first firing was determined based on the X-ray diffraction spectrum. As a result, the content of impurities in each example was 1% or less in terms of oxide.

[0060] [Specific surface area of ​​powder] The powders (before sintering) obtained after the first firing of each example were measured for specific surface area (m2) in accordance with JIS R 1626:1996 "Method of measuring specific surface area of ​​fine ceramic powder by gas adsorption BET method". 2 As a result, the specific surface area of ​​the lanthanum-molybdenum composite oxide powders of Examples 1 to 3 was 3.0 m 2 / g.

[0061] [Contact angle] In order to evaluate the water repellency of the sintered bodies of the Examples, the contact angle (°) was measured in accordance with JIS 3257:1999 "Test method for wettability of substrate glass surface." The measurement results are shown in Table 1.

[0062] [Identification of crystalline phases using powder XRD (2)] The sintered bodies of the Examples were pulverized using an agate mortar and pestle to obtain pulverized products. These pulverized products were pulverized products of the sintered bodies, and were powders obtained after the second firing. The pulverized products of the Examples were then subjected to the above-mentioned powder X-ray diffraction method to identify the crystal phase. The results of the X-ray diffraction spectrum of the Examples (after sintering) are shown in Figs. 5 and 6, and the results of identifying the crystal phase are shown in Table 1.

[0063] [Antibacterial performance evaluation] The lanthanum-molybdenum composite oxide powder of Example 3 was subjected to an antibacterial performance evaluation test in accordance with JIS Z 2801:2012. Specifically, Staphylococcus aureus was used as the test bacteria, and the antibacterial activity value R was obtained after 2 hours, 4 hours, and 6 hours. The antibacterial activity value R was obtained for each action time (2, 4, or 6 hours) from R=Ut-At. Ut is the logarithmic value (average value) of the number of viable bacteria at each action time t (2, 4, or 6 hours) in the untreated test sample, and At is the logarithmic value (average value) of the number of viable bacteria at each action time t (2, 4, or 6 hours) in the treated test sample. The number of samples for each test sample was 3.

[0064] The inoculum concentration was 2.6 x 10 6 cfu / ml, the number of viable bacteria when the inoculum volume is 0.1 ml per sample (cfu / cm 2 ) were counted.

[0065] The lower detection limit (definition) in the antibacterial performance evaluation is as follows. If the number of live bacteria at 0 hours is N0 and the number of live bacteria at t hours is N, the common logarithm of the viable bacteria survival rate N / N0 is expressed as log(N / N0). Time t is the duration of action. If the antibacterial activity value R is 2.0 or more (i.e., R≧2.0), but Log(N t / N0)-Log(N t+2 / N0)≦0.5, Log(N t / N0) and Log(N t+2 / N0), whichever is smaller, shall be the detection limit.

[0066] The results of the antibacterial performance evaluation (time to reach the lower limit of detection, antibacterial activity value R) are shown in Table 2. Note that even if the lower limit of detection is not reached, Log(N t / N0)-Log(N t+2 If / N0)>0.5, the detection limit is set to "6 hours or more" and Log(N t / N0)-Log(N t+2 In the case of / N0)≦0.5, this is not described in Non-Patent Document 1, and is therefore indicated as “-” in Table 2.

[0067] [Antiviral performance evaluation] For the lanthanum-molybdenum composite oxide powder of Example 3, an antiviral performance evaluation test was conducted in accordance with JIS R 1756:2013 "Visible light responsive photocatalyst, antiviral (bacteriophage)". Specifically, bacteriophage Qβ was used as the test virus, and the antiviral activity values ​​(in the dark) V after 2 hours, 4 hours, and 6 hours were measured. D The antiviral activity value (in the dark) V D V for each time period (2, 4 or 6 hours) D =Log(U D )-Log(T D ) was calculated. Log(U D ) is the logarithm (average) value of the number of phages in the untreated test sample after each exposure time (2, 4 or 6 hours), and Log(T D) is the logarithmic value (average value) of the number of phages in the processed test product after each exposure time (2, 4 or 6 hours). The number of samples for each test product is 3.

[0068] The concentration of the inoculated phage solution was 2.3 × 10 7 cfu / ml, the number of phages (infectivity value) when the inoculation volume of the inoculated phage solution is 0.1 ml per sample (cfu / cm 2 ) were counted.

[0069] The lower detection limit (definition) in the evaluation of antiviral performance is as follows. If the number of phages (infection value) at 0 hours is N'0, and the number of phages (infection value) at t hours is N', the common logarithm of the phage survival rate N' / N'0 is expressed as log(N' / N'0). Time t is the duration of action. Antiviral activity value V D The value of is 3.0 or more (i.e., V D ≧3.0), Log(N' t / N'0)-Log(N' t+2 / N'0)≦0.5, Log(N' t / N'0) and Log(N' t+2 / N'0), whichever is smaller, shall be the detection limit.

[0070] Antiviral performance evaluation results (time to reach lower limit of detection, antiviral activity value V D ) are shown in Table 2. Note that even if the detection limit is not reached, Log(N' t / N'0)-Log(N' t+2 When / N'0)>0.5, the detection limit was set to "6 hours or more."

[0071] The results of the antibacterial performance evaluation (literature values) and the antiviral performance evaluation (literature values) for the powder before sintering in Comparative Example 1 and the powder after sintering in Comparative Example 1 (pulverized sintered body) are also shown in Table 2.

[0072] [Table 1]

[0073] [Table 2]

[0074] [Crystal phase, etc.] Fig. 1 shows the X-ray diffraction spectra of the lanthanum-molybdenum composite oxide powder of Example 1. As shown in Fig. 1, the lanthanum-molybdenum composite oxide of Example 1 contains La2Mo2O9 as a main crystal phase and La2Mo3O as a sub-crystal phase before sintering. 12 and La2O3. As shown in Fig. 1, the ratio (Y / X) of the intensity X of the largest diffraction peak (30.6°) among the peaks derived from the main crystal phase that do not overlap with the peaks of the sub-main crystal phase to the intensity Y of the largest diffraction peak (29.9°) among the peaks derived from the sub crystal phase that do not overlap with the peaks of the main crystal phase is 1.2.

[0075] Fig. 5 is an X-ray diffraction spectrum of the sintered body of Example 1. As shown in Fig. 5, the lanthanum-molybdenum composite oxide of Example 1 contains La2Mo2O9 as a main crystal phase and La2Mo3O 12 , La7Mo7O 30 and La2O3. As shown in Fig. 5, the ratio (Y / X) of the intensity X of the largest diffraction peak (24.9°) among the peaks derived from the main crystalline phase that do not overlap with the peaks of the sub crystalline phase to the intensity Y of the largest diffraction peak (33.1°) derived from the sub crystalline phase is 0.06.

[0076] Fig. 2 is an X-ray diffraction spectrum of the lanthanum-molybdenum composite oxide powder of Example 2. As shown in Fig. 2, the lanthanum-molybdenum composite oxide of Example 2 contains La2Mo2O9 as a main crystal phase and La2Mo3O 12As shown in FIG. 2, the ratio (Y / X) of the intensity X of the largest diffraction peak (30.6°) among the peaks derived from the main crystalline phase that do not overlap with the peaks of the sub crystalline phase to the intensity Y of the largest diffraction peak (29.9°) among the peaks derived from the sub crystalline phase that do not overlap with the peaks of the main crystalline phase is 0.13.

[0077] Fig. 6 is an X-ray diffraction spectrum of the sintered body of Example 2. As shown in Fig. 6, the lanthanum-molybdenum composite oxide of Example 2 contains La2Mo2O9 as a main crystal phase and La2Mo3O 12 and La2O3.

[0078] Fig. 3 shows the X-ray diffraction spectra of the lanthanum-molybdenum composite oxide powder of Example 3. As shown in Fig. 3, the lanthanum-molybdenum composite oxide of Example 3 contains La2Mo2O9 as the main crystal phase and La2Mo3O 12 , LaMo2O5, and La2O3. As shown in Fig. 3, the ratio (Y / X) of the intensity X of the largest diffraction peak (30.7°) among the peaks derived from the main crystal phase that do not overlap with the peaks of the sub crystal phase, to the intensity Y of the largest diffraction peak (29.9°) among the peaks derived from the sub crystal phase that do not overlap with the peaks of the main crystal phase, is 0.08.

[0079] Fig. 7 is an X-ray diffraction spectrum of the sintered body of Example 3. As shown in Fig. 7, the lanthanum-molybdenum composite oxide of Example 3 contains La2Mo2O9 as a main crystal phase and La6MoO 12 and La2O3.

[0080] 4 is an X-ray diffraction spectrum of the lanthanum-molybdenum composite oxide powder of Comparative Example 2. As shown in FIG. 4, the lanthanum-molybdenum composite oxide of Comparative Example 2 has LaMo as the main crystal phase before sintering.0.98 O 4.07 As a secondary crystalline phase, La6Mo8O 33 and La2O3.

[0081] [Contact angle] As shown in Table 1, the sintered bodies of Examples 1 to 3 had a contact angle with water of 103°. Thus, it was confirmed that the sintered bodies of Examples 1 to 3 were water repellent, like the sintered body of Comparative Example 1.

[0082] [About antibacterial and antiviral properties] As shown in Table 2, in the antibacterial and antiviral evaluations, the lanthanum-molybdenum composite oxide powder of Example 1 reached the lower limit of detection in two hours. In contrast, in the case of the powder of Comparative Example 1 (powder before sintering), the lower limit of detection was reached in four hours in both the antibacterial and antiviral evaluations (see Non-Patent Document 1). Thus, it was confirmed that the lanthanum-molybdenum composite oxide powder of Example 1 has superior antibacterial and antiviral properties compared to Comparative Example 1.

Claims

1. La 2 M.O. 2 O 9 is the main crystal phase, and 2 M.O. 2 O 9 The lanthanum-molybdenum composite oxide other than the above is used as a secondary crystal phase, The lanthanum-molybdenum composite oxide, wherein the secondary crystal phase contains at least one selected from the group consisting of La2Mo3O12, La6MoO12, La2Mo4O15, La2MoO6, La4MoO9, and LaMo2O5.

2. 2. The lanthanum-molybdenum composite oxide according to claim 1, wherein a ratio of an intensity X of the largest diffraction peak among the diffraction peaks attributable to the main crystal phase and not overlapping with any peaks of the sub crystal phase in an X-ray diffraction spectrum obtained by a powder X-ray diffraction method to an intensity Y of the largest diffraction peak among the diffraction peaks attributable to the sub crystal phase and not overlapping with any peaks of the main crystal phase satisfies Y / X<1.

3. An antibacterial sintered body obtained by sintering the lanthanum-molybdenum composite oxide described in claim 1 or claim 2.

4. An antiviral sintered body obtained by sintering the lanthanum-molybdenum composite oxide described in claim 1 or claim 2.

Citation Information

Patent Citations

  • Method for synthesizing solid oxide fuel battery electrolyte material nano lanthanum molybdate

    CN106745261A

  • Lanthanum molybdate (La2Mo2O9) moderate temperature conductor material and its preparation method

    CN1962460A

  • Compounds derived from la2mo2o9 and their use as ion conductors

    JP2003530291A

  • Production of compounds containing a combination of two crystalline phases

    JP2009526730A

  • Substances with antibacterial properties

    JP2010509385A